Inhibition of NF-kB Pathway by Gggulsterone in the Protective Effects of Cyclophosphamide-Induced Renal Toxicity - M. Al-joda, Ali; Zalzala, Munaf H. (Iraqi Journal of Pharmaceutical Sciences, 2019)
Cyclophosphamide which acts as cytotoxic alkylating agent can induce a renal damage through the toxic metabolites which result from metabolic activation of Cyclophosphamide by cytochrome P-450 inside hepatocyte and develop renal toxicity by direct binding with cellular organelles in the urinary tract cells. Guggulsterone is a sterol derived from plant has ability to bind to farsenoid X receptor, mineral corticosteroid receptor, androgen receptor, glucocorticoid receptor and estrogen receptor.